Sub-activity analysis by using wristband-type wearable health devices to measure construction workers’ physical demands - Wang, Jiayao; Seo, JoonOh; Gong, Yue; Siu, Ming-Fung Fransic; Hwang, Sungjoo; Khan, Masood (Journal of Civil Engineering and Management, 2025)
Understanding and managing the physical demands of construction workers is critical to their safety, health, and productivity. Construction tasks, especially cyclic and non-cyclic activities are highly variable. Cyclic tasks involve repetitive actions, which if not well-distributed, can lead to cumulative fatigue and long-term health issues. Conversely, non-cyclic tasks are unpredictable and irregular, making it challenging to allocate workloads effectively. Despite these challenges, few studies have investigated continuous physical demands for both task types, particularly in dynamic, onsite construction environments. Filling this gap is essential for developing practical strategies to improve workload allocation, mitigate health risks, and optimize workforce management. This study addresses this critical gap by using lightweight wearable wristbands equipped with heart rate (HR) biosensors to monitor workers’ activities without disrupting their tasks. The percentage of heart rate reserve (%HRR) is calculated to quantify the continuous physical demands of 10 construction workers performing both cyclic and non-cyclic tasks across two construction sites over three weeks. Results revealed significant workload variations between task types and work patterns. For instance, stationary tasks (‘work without moving’) strongly influenced %HRR for rebar workers, while dynamic tasks (‘work with moving’) had a greater impact on form workers. Additionally, while some daily average %HRR values fell below the 33% threshold, extended high-intensity periods (exceeding 40% HRR for over 30 minutes) posed potential health and safety risks for construction workers. This research demonstrates the potential of long-term HR monitoring to address workload disparities, ensure balanced task allocation, and reduce health risks for construction workers.